A Study on Impact of Electronics Government Procurement on Procurement Effectiveness of the Building Construction Works at Jumla - Budthapa, Birendra Bahadur; Neupane, Uttam; Bhattarai, Subash Kumar; Sharma, Socrates Bhattarai (International Journal on Engineering Technology and Infrastructure Development, 2024)
E-procurement is the modern way of using electronic tools, such as the Internet and e- mail for business-to-business purchases online. Besides, it also helps to supply and provide services for sales online using Internet-based technology and can be a tool used by all governments to promote more extensive reforms in the areas of advancing the social, technological, and economic infrastructure. Procurement of construction works, goods and services electronically in addition will increase transparency and accountability, improve standardization and healthy competition, reducing usage of paper and hard copy documentation as well as improving the efficiency, effectiveness of the procurement process. E-Procurement implementation at the building construction work at Jumla district level in some impact i.e., processing time reduce; accessibility increase was bothered by low as compared with cost saving and increasing transparency but all included impact on structural questionnaire is reliable (Reliable test value = 0.987) on procurement of building construction work. Methods of data analysis used in this research are by using a software program SPSS (Statistical Package for the Social Sciences) to examine the relationship between variables. RII (Relative Importance Index) ranked introduced impact of e-GP on procurement efficiency. The population used in this study are clients, consultants and contractors who are directly involved in procurement of building construction work of Jumla district. Finally, Nepalese construction industry should focus on adopting electronic procurement on all construction work by facilitating IT & ICT infrastructure to more significantly enhanced the procurement effectiveness construction industry.